2011
DOI: 10.7150/ijbs.7.440
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pluripotency Genes in the Fish Medaka

Abstract: Stem cell cultures can be derived directly from early developing embryos and indirectly from differentiated cells by forced expression of pluripotency transcription factors. Pluripotency genes are routinely used to characterize mammalian stem cell cultures at the molecular level. However, such genes have remained unknown in lower vertebrates. In this regard, the laboratory fish medaka is uniquely suited because it has embryonic stem (ES) cells and genome sequence data. We identified seven medaka pluripotency g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 52 publications
7
62
0
Order By: Relevance
“…This might be because of the divergence of gene regulation between lower and high vertebrates during evolution. Zygotic transcription of Klf4 is detected in both lower vertebrate and mammalian early embryos, but the abundance of zygotic transcripts is lower than maternal ones, as revealed in Xenopus and medaka fish (Wang et al, 2011). Ubiquitous transcription of Klf4 in early cleavage, blastula and gastrula embryos fits well with its function in germ-layer formation described in the present study.…”
Section: Klf4 Is Required For Germ-layer Differentiationsupporting
confidence: 71%
See 1 more Smart Citation
“…This might be because of the divergence of gene regulation between lower and high vertebrates during evolution. Zygotic transcription of Klf4 is detected in both lower vertebrate and mammalian early embryos, but the abundance of zygotic transcripts is lower than maternal ones, as revealed in Xenopus and medaka fish (Wang et al, 2011). Ubiquitous transcription of Klf4 in early cleavage, blastula and gastrula embryos fits well with its function in germ-layer formation described in the present study.…”
Section: Klf4 Is Required For Germ-layer Differentiationsupporting
confidence: 71%
“…Xenopus Klf4 is maternally expressed. In mammals, there is little maternal transcript of Klf4 according to microarray data (Hamatani et al, 2008); however, significant maternal inheritance of Klf4 is observed in medaka and zebrafish (Wang et al, 2011;Li et al, 2011;Luo et al, 2011). This might be because of the divergence of gene regulation between lower and high vertebrates during evolution.…”
Section: Klf4 Is Required For Germ-layer Differentiationmentioning
confidence: 91%
“…The protein sequence of this gene was shown to be poorly conserved among vertebrates with the exception of the homeodomain region. In contrast to mammals, the nanog transcript was found to be maternally inherited in medaka (Camp et al, 2009;Wang et al, 2011). In addition, the specific role of Nanog in cell lineage commitment was suggested to be different between medaka and mammals.…”
Section: Introductionmentioning
confidence: 78%
“…It was postulated that Nanog is an amniote-specific gene and is absent from anamniotes and invertebrates [25]. However, Nanog homologs have recently been reported for the teleost fish (medaka) [27,28] and for the urodele amphibian axolotl [29]. It was suggested that the mechanisms governing pluripotency might be conserved from urodele amphibians to mammals [29].…”
Section: Introductionmentioning
confidence: 99%